Research on Pathways to Desistance (Maricopa County, AZ and Philadelphia County, PA): Collateral Measures, 2000-2004 - Mulvey, Edward P. ([Verlag nicht ermittelbar], 2013)
The Pathways to Desistance study was a multi-site study that followed 1,354 serious juvenile offenders from adolescence to young adulthood in two locales. Enrolled into the study were adjudicated youths from the juvenile and adult court systems in Maricopa County (Phoenix), Arizona (N=654) and Philadelphia County, Pennsylvania (N=700) from 2000 through 2010.This study looks at interviews conducted with the collateral informants who participated in the study. The collateral informants were nominated by the main study participant and represented individuals who "knew the study participant well". At the interview baseline the collateral informant was usually a biological parent. During the three follow-up interviews the majority of collaterals were a friend. Collateral informants could also be a sibling, significant other, or relative. Collaterals were asked questions in regards to the main study participant's life, allowing for comparison between responses provided by two sources. A baseline interview was conducted with the collateral after the baseline interview took place with the main participant. Additional waves of follow-up with collaterals took place at 12, 24, and 36 months. A collateral report is not present for all of the main study participant interviews across waves (see response rate below).